Oxygen therapy improves energy metabolism in focal cerebral ischemia - Sun, Li; Strelow, Hartmut; Mies, Günter; Veltkamp, Roland (Brain research, 2011)
Oxygen therapy (OT) with hyperbaric oxygen (HBO) or normobaric hyperoxia (NBO) improves the oxygenation of penumbral tissue in experimental ischemic stroke. However, whether this results in the improvement of energy metabolism is unclear. We investigated the effect of both OTs on tissue acidosis and on ATP production. Beginning 25min after filament middle cerebral artery occlusion (MCAO), mice breathed either air, 100% O2 (NBO), or 100% O2 at 3 ata (HBO) for 60min. Regional tissue pH was measured using the umbelliferone fluorescence. Regional ATP concentration was depicted by substrate-specific bioluminescence. Severity of ischemia did not differ among groups in laser-Doppler flowmetry. Both NBO (70.1±14.0mm3) and, more effectively, HBO (57.2±11.9mm3) significantly reduced volume of tissue acidosis compared to air (89.4±4.0mm3, p<0.05). Topographically, acidosis was less pronounced in the medial striatum and in the cortical ischemic border areas. This resulted in significantly smaller volumes of ATP depletion (77.8±7.7mm3 in air, 61.4±15.2mm3 in NBO and 51.2±14.4mm3 in HBO; p<0.05). In conclusion, OT significantly improves energy metabolism in the border zones of focal cerebral ischemia which are the areas protected by OT in this model.